P178 Remote monitoring as an effective management strategy in inflammatory bowel disease: the lesson from COVID-19 pandemic. (27th May 2021) - Busacca, A; Sinagra, E; Guida, L; Carrozza, L; Melodia, M; Maida, M; Battaglia, S; Celsa, C; Cammà, C; Cappello, M
Abstract: Background: During the COVID-19 outbreaks many IBD clinics in Italy adopted a remote monitoring approach both to ensure an adequate follow-up of patients with inflammatory bowel disease (IBD) and respect the rules of social distancing, while access to hospital was restricted. Aim of the study was to perform a survey on IBD patients submitted to remote monitoring in our tertiary referral center in order to assess adherence and patients' perceptions and satisfaction as well as their opinions for future monitoring. Changes in disease activity and Quality of Life were also evaluated. Methods: Consecutive patients with IBD scheduled for follow-up visits were switched to remote monitoring through e-mail from March 2020 to February 2021, Patients were asked to complete a questionnaire focusing on 3 elements of the intervention: (1) self-assessment questions, (2) action plans, and (3) educational messages. With regards to self-assessment questions, we used the SIBDQ (to evaluate the QoL) and the IBDSI (to evaluate symptoms as patients' reported outcomes). All patient sent by email results of blood texts: ESR, CRP, CBC, faecal calprotectin, ferritin, serum iron. HBI Index and Mayo UC score were calculated by the treating physicians. Results: 424 subjects, 100% Caucasians, completed the survey. 233 (55, 1%) were male, 220 (52.0%) had Crohn's Disease (CD). Median baseline Mayo Score and Harvey Bradshaw Index were 3 and 4, respectively. 9 (2, 1%) patients were referred to emergency department because of disease flares. 2 (1%) UC patients needed to add topical therapy, 9 (4%) CD patients started therapy with systemic steroids and 3 (1, 3%) with biologics. 410 (96, 9%) patients were satisfied about telemedicine, and 320 (76, 5%) patients reported that would maintain this approach also after COVID-19 outbreak. On univariate logistic regression analysis, only a high ferritin value was found to be related to patients' satisfaction (p=0.001). Lower calprotectin (p=0.012) and need for treatment change (p<0001) were found to be related to QoL, while CD (p=0.052), age (p=0.027), disease duration (p=0.046) and higher calprotectin (p=0.021) were associated to the need for treatment change. None of the variables were significant on multivariate analysis. Conclusion: Our results confirm in an homogeneous cohort of IBD patients from southern Italy that a telemedicine approach can substitute face-to-face consultations at least for patients in remission or mild clinical activity. Patients'outcomes were not affected as far as concerns referral to emergency services or the use of steroids for disease flares. A high proportion of patients would maintain this management strategy.